PENGARUH KINERJA KEUANGAN DAN KONDISI MAKROEKONOMI TERHADAP PEMBIAYAAN BERMASALAH BPR SYARIAH DI INDONESIA - Fatoni, Ahmad; Utami, Kurnia Dwi Sari (EQUILIBRIUM, 2019)
This study is to evaluate the bank performances and macroeconomic conditions to the NPF. Internal factors consist of Capital Adequacy Ratio (CAR), Financing to Deposits Ratio (FDR), Return on Assets (ROA), operating income operating expenses (BOPO), dummy Loan to Value (LTV) and Profit and Loss Sharing (PLS). While the external factors are IHK, Gross Domestic Product (GDP) and BI rate/BI7DRR. This research uses the Autoregressive Distributed Lag (ARDL) method. The research sample is the monthly BPR Syariah data in Indonesia from January 2010 to June 2018. The results are variable NPF, CPI, GDP, BI rate, CAR, BOPO, LTV and PLS long-term cointegration to NPF. While the long term results of CPI, GDP, CAR, FDR, and PLS affect the NPF